Conceptions of environmental education of teachers of the Municipal Education Network of Aracaju-SE - Fonseca, Mariana Reis; Nepomuceno, Aline Lima de Oliveira; Santos, Hevely Catharine dos Anjos (Debates em Educação, 2023)
Environmental Education (EE) enables awareness, critical consciousness and active positioning in relation to socio-environmental issues. Therefore, this article aims to understand conceptions about EE of teachers of the municipal education network of Aracaju, Sergipe State, Brazil. For that purpose, we conducted semi-structured interviews and analyzed the responses based on Discursive Textual Analysis. Conceptions are superficial and individualistic, reinforcing the fragmented and conservative socio-environmental educational practice, enhanced by a technical curriculum.